Test volume mitigation for mobile devices software development: An improvement approach considering shared requirements - Andrade, Paulo; Marques, Kathrian; Ribeiro, Luiz; Silva, Marcelo da; Fragata, Hendria; Oliveira, Adriano; Nogueira, Juan (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST), 2023)
The number of software variations that are embedded in mobile devices is growing. Due to the high demand for software adaptation, manufacturers need to find strategies to ensure the quality of the software they embed. In an attempt to reduce software test workload after requirements implementations, we propose an improvement to a process we use at SIDIA R&D Institute. Our approach is based on testing each requirement, instead of the current process, which consists of tests repeated for each client. Our experiments’ results are based on a small set of device models and show that gains obtained can be expanded to the entire device models portfolio. Additionally, the proposed improvement can greatly reduce requirements testing time. We performed our experiments in a real scenario, so the results may be affected by variables out of study scope, specially for the fourth experiment, which was performed on new device models, where some stability work still may be required.